The role of digestibility in the selection of spring feeding sites by Brent Geese - Boudewijn, T (Wildfowl, 1984)
In spring, staging Dark-bellied Brent Geese Branta bernicla bernicla show a marked shift in feeding site preference from improved grassland before mid-April to salt-marsh in May. Using two groups of three captive Brent Geese each, the changes in digestibility were studied from March until the end of May in both vegetation types. There was no difference in selectivity and digestive capacity between the captive birds and their wild counterparts. The earlier growth of improved grassland as opposed to salt-marsh resulted in a higher digestibility of the former until mid-April, but later the digestibility dropped as the grass started to flower. Spring growth of the salt-marsh vegetation lagged behind, resulting in a higher digestibility in May. In this way the highest quality food is available on the lower salt-marshes exactly when the Brent are building up their body reserves to migrate to, and breed on, the high-arctic tundras of Siberia.